KINERJA BANK DENGAN RASIO CAMEL TERHADAP PRAKTIK MANAJEMEN LABA - Wattimena, Fransina (Jurnal Keuangan dan Perbankan, 2012)
This study aimed to measure the performance of the bank by using camel ratio to earnings managementpractices. This research objects used cluster danamon bank ambon total of 14 samples of banks consisting of 2banks conventional danamon and 12 savings and loan business unit danamon using data for 2006-2011. Theresults of studies using T test showed that there had no significant effect between the performance of the bankto the practice of earnings management measured using discretionary accruals in Danamon banks. The resultby using multiple regression analysis showed that there was a significant negative impact on earnings managementpractices. Thus cluster ambon danamon bank had to use earnings management practices.